Gaston Bachelard et la psychanalyse. Rencontres, transformations et usages - Becerra Batán, Marcela Renée (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
Called to think from the expression : « Gaston Bachelard vis-à-vis Psychoanalysis », in this work I return to this complex question and propose a journey around Bachelard’s encounters with Psychoanalysis, as well as the transformations that Bachelard carries out. I will try to show redefinitions, recreations of concepts, criticisms, convergences and divergences, distances, and approaches ; in short, unique uses of Psychoanalysis that Bachelard makes for a philosophical purpose, original in his time and still current : account for the activity of the imagination, but also and in a complementary way, of the activity of scientific reason.